Implementation of Problem Based Learning Model on Function Transformation Material to Improve Student Learning Outcomes - Wasilatus saniyah; Dwi Rahayu ningsih; Moh. syadidul itqan (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This research is a Classroom Action Research (CAR) aimed at improving students’ learning outcomes on the topic of function transformation through the implementation of the Problem Based Learning (PBL) model in Grade XII of MA Islamiyah Syafi’iyah during the 2024/2025 academic year. The research subjects consisted of 19 students. The study was conducted in two cycles, each consisting of four stages: planning, implementation, observation, and reflection. The data collection instruments included learning achievement tests and observation sheets for both student and teacher activities. The success indicator of this study was determined if at least 75% of the students achieved the Minimum Mastery Criterion (KKM) of 75, and there was an improvement in the average learning outcome in each cycle. The results showed that students’ learning outcomes improved after the implementation of the PBL model. In Cycle I, the percentage of students who achieved mastery was 52.63% with an average score of 72.11. After the improvements made in Cycle II, the mastery percentage increased to 84.21% with an average score of 79.32. These findings indicate that the Problem Based Learning model can effectively enhance students’ learning outcomes on the topic of function transformation. In conclusion, the Problem Based Learning (PBL) model is effective in improving students’ mathematics learning outcomes, particularly in function transformation material, as it encourages student activeness, develops critical thinking skills, and facilitates conceptual understanding through contextual problem-solving activities.